Correlates of HIV seropositivity in young West and Central African women: a pooled analysis of 17 demographic and health surveys - Bommer, Christian; Vollmer, Sebastian; Zagre, Noël Marie (Journal of global health, 2021)
Background Young women in West and Central Africa have been described by the United Nations as being especially vulnerable to HIV/AIDS. Despite a consensus that increased efforts are necessary to address the needs of this particular demographic, correlates of HIV seropositivity in young West and Central African women have not been systematically described. This study fills this gap using a rich set of publicly available survey data. Methods For this cross-sectional study, we combined HIV test results for young women (age 15-24 years) with information on demographic, cultural and socioeconomic correlates from 17 recent Demographic and Health Surveys (DHS) to estimate odds ratios (OR) from fixed effects logistic regression models accounting for potential individual, household-level and contextual risk factors of HIV seropositivity. Results The prevalence of HIV seropositivity among young women is higher than for men of the same age in all included surveys, except for the Burkina Faso DHS. An important correlate of HIV seropositivity in young women is early sexual activity (OR = 1.510; 95% confidence interval (CI)=1.100, 2.072), while higher education is associated with reduced odds of being HIV positive (OR= 0.215; 95% CI= 0.057, 0.820). No significant correlation has been found for individual HIV awareness, but HIV stigma is negatively associated with HIV seropositivity (OR= 0.495; 95% CI = 0.247, 0.990, in the fully adjusted model). Conclusions The results demonstrate the need to design effective policies addressing behavioral risks in young women. In particular, increasing HIV awareness alone is likely to be insufficient. Instead, information campaigns need to focus on transforming awareness into behavioral change. Moreover, fostering formal education may be an effective tool in the fight against HIV/AIDS.